2013
DOI: 10.1037/a0027009
|View full text |Cite
|
Sign up to set email alerts
|

An examination of parental self-efficacy among mothers and fathers.

Abstract: Sevigny and Loutzenhiser, in their 2010 examination of parental self-efficacy (PSE) in fathers, did not identify data supporting the importance of self-efficacy beliefs in the paternal parenting role. However, a task-specific measure of PSE was used, and because the tasks mothers and fathers typically perform differ, task-specific measures may not be applicable to both mothers and fathers. The present study addressed this limitation by using a domain PSE measure (where specific tasks are not identified) in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 67 publications
2
66
1
7
Order By: Relevance
“…Mothers might be more involved in these specific behaviors than are fathers, and therefore their PSE might be more strongly related to such parenting practices than are fathers' PSE. Fathers' PSE has, instead, been associated with fathers' exertion of control (Murdock, 2012), suggesting that among fathers, PSE might be more strongly linked to practices aiming at disciplining or correcting the child than to behaviors similar to those used in this study.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Mothers might be more involved in these specific behaviors than are fathers, and therefore their PSE might be more strongly related to such parenting practices than are fathers' PSE. Fathers' PSE has, instead, been associated with fathers' exertion of control (Murdock, 2012), suggesting that among fathers, PSE might be more strongly linked to practices aiming at disciplining or correcting the child than to behaviors similar to those used in this study.…”
Section: Discussionmentioning
confidence: 74%
“…When comparisons have been made, the results have shown that children's problematic behaviors are linked more strongly to mothers' PSE than to fathers' PSE (Meunier & Roskam, 2009;Murdock, 2012;Slagt et al, 2012). One explanation offered for this difference concerns the level of involvement in child rearing activities.…”
Section: Practices and Adolescents' Behaviorsmentioning
confidence: 94%
See 2 more Smart Citations
“…This particular variable has been the focus of extensive research, demonstrating its robust protective and adaptive impact on parenting (Giallo, Treyvaud, Cooklin, & Wade, 2013;Murdock, 2013); parent functioning (Bloomfield & Kendall, 2012;Kendall, Bloomfield, Appleton, & Kitaoka, 2013;Leahy-Warren, McCarthy, & Corcoran, 2012); and, most importantly, improvements in children's social, physical, and academic wellbeing (Bandura, Barbaranelli, Caprara, & Pastorelli, 1996;Leahy-Warren et al, 2012;Sanders & Woolley, 2005;Shumow & Lomax, 2002).…”
mentioning
confidence: 99%